Need Analysis of MOOCs-Based Learning Media Development to Improve Student Motivation - Bukman Lian; Bebby Rino Oksatianti; Eko Risdianto; Afrizal Mayub (AL-ISHLAH: Jurnal Pendidikan, 2021)
The development of MOOCs-based learning media is essential for increasing student motivation. This study aims to analyze the needs of developing MOOCs-based learning media to increase students' motivation on temperature and heat material. This type of research is survey research and literature study as a basis for further development research. The research instrument used was a needs analysis questionnaire with 17 questions given to 75 respondents from SMA Negeri 1, SMA Negeri 6, and SMA Negeri 9 Bengkulu. In this study, data analysis used descriptive statistics. Based on the results of the study obtained data that can be concluded that currently, students need the development of learning media based on MOOCs to increase student motivation on temperature and heat material. This study concluded that the development of MOOCs-based learning media to increase students' motivation on the material of temperature and heat is needed in learning. Overall, this research implies that MOOCs-based learning media is needed to increase students' motivation, especially in learning the material of temperature and heat. The implications in learning other materials are highly recommended to be implemented to use the given learning media to gain effectiveness in learning activities, especially in learning the material of temperature and heat.